A systems dynamics investigation into the impact of capacity limitations on the Bullwhip effect in a closed-loop system with remanufacturing - Tombido, Locadia Linda (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.